A general equilibrium analysis of the effects of the 2014-2020 European Cohesion policy in the Portuguese regions - Javier Barbero; Simone Salotti (European Commission, Joint Research Centre (JRC), 2021)
We analyse the impact of the investments related to the European Cohesion policy in Portugal over the 2014-2020 programming period. We use the spatial dynamic general equilibrium model RHOMOLO to identify the direct and indirect effects stemming from a variety of spending categories and economic channels. The policy interventions are modelled with both demand and supply side shocks exerting short and long run effects, the latter being related to changes in labour productivity, transport costs, and total factor productivity. An important part of the analysis deal with the spillovers spreading the effects of the policy outside the borders of the regions in which the investments take place. Our results show that the exteuro30 billion of Cohesion policy investments can increase Portugal's GDP by 3.5% at the end of the implementation period, and that additional benefits in terms of GDP and employment continue to materialise after the end of the monetary injections. Moreover, we present region-, Fund-, and field-of-intervention-specific results to give a complete picture of the impact of Cohesion policy in Portugal.
Keywords: C68; R13; 330; RHOMOLO; region; growth; cohesion policy; Portugal